From threats to solutions: A literature review of climate adaptation in anadromous salmon and trout - Lisa G. Crozier; Jared E. Siegel (Ecosphere)
Abstract Understanding the evolutionary responses of anadromous salmon and trout to climate change is critical for effective conservation planning. In this study, we conducted a comprehensive review of literature published from 2010 to 2020 to synthesize current knowledge on climate impacts to these fish populations. Specifically, we focused on 199 papers that explored evolutionary processes in response to changing environmental conditions. Our analysis revealed several key themes, including the interwoven influences of climate and human activities on genetic variation, phenotypic traits, and population dynamics. We found that geographic patterns in genetic diversity are closely linked to climatic gradients, highlighting the importance to conservation strategies of variation in existing adaptive capacity. Additionally, temporal trends in phenology, maturation age, and fecundity indicate ongoing evolutionary and plastic responses to climate change. Importantly, human activities were identified as significant drivers of maladaptation in anadromous salmon and trout populations. We emphasize the need for targeted monitoring of specific evolutionary processes to mitigate the loss of genetic diversity and enhance adaptive capacity. Our study underscores the importance of identifying and protecting areas of high genetic diversity and rare genes, particularly in regions projected to experience rapid climatic shifts. In conclusion, our findings identify strengths and gaps in the research investigating the role of evolutionary dynamics in the face of climate change. By capitalizing on new tools for sequencing, genomic analysis, and automated field data collection, we can establish baselines for tracking evolutionary responses to climate change. Better integration of evolutionary processes into projections of future climate impacts will lead to more effective strategies to ensure the long‐term resilience of these iconic fish species and other wildlife.